Functional differentiation of chitinases in the white-rot fungus Phanerochaete chrysosporium. (August 2016) - Karlsson, Magnus; Stenlid, Jan; Lindahl, Björn
Abstract: Enzymes that act on chitin, including glycoside hydrolases (GH) family 18 (chitinases) and family 20 (NAGases), may have multiple roles in fungal biology. Here, we describe the number, structure and expression of the eleven GH18 and four GH20 genes identified in the wood-rotting basidiomycete Phanerochaete chrysosporium, and measure endochitinase and NAGase activities in situ . A phylogenetic analysis placed a predicted Chi18D protein in a separate, novel subgroup that was named B-VI. Chitinolytic activity was induced at the hyphal front of P . chrysosporium both during combative interactions with Heterobasidion irregulare and during secondary colonization of dead H . irregulare mycelium. Gene expression of chi18I and chi18K was induced during combative interactions with H . irregulare, but not during secondary colonization of dead mycelium. In conclusion, our data suggests that P . chrysosporium uses a consortium of different chitinolytic enzymes for nutrient acquisition and for defence of territorial boundaries. Highlights: Chitinase and NAGase genes are identified in Phanerochaete chrysosporium . A novel phylogenetic subgroup of chitinases is described. Chitinolytic activity in P . chrysosporium is induced during interspecific interaction. Two chitinase genes are induced in P . chrysosporium during combative interaction.